2006
DOI: 10.1063/1.2186374
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the influence of charge traps on single-layer organic light-emitting diode efficiency

Abstract: We investigate theoretically the role of carrier trapping on the efficiency of single-layer organic light-emitting diodes (OLEDs) by incorporating traps into the OLED device model of Davids et al. [J. Appl. Phys. 82, 6319 (1997)]. Carrier trapping directly affects the density and mobility balance between electrons and holes through its effects on injection and mobility. In addition, trap-mediated changes in density alter recombination rates and spatial profiles of recombination that become important when excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In a previous paper, 5 in order to investigate the important role of charge carrier trapping on the efficiency of singlelayer OLEDs, we extended the device model by Davids et al [2][3][4] describing charge injection, transport, and recombination in these devices to account for charge trapping in the organic material and the effects of luminescence quenching in the region adjacent to a metal electrode. Device simulations were used to demonstrate the influences of trapping on device efficiency through their effects on charge balance, mobility balance, recombination rate, and the location of the recombination region when quenching at metallic contacts is important.…”
Section: The Effects Of Energetic Disorder and Polydispersity In Conjmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous paper, 5 in order to investigate the important role of charge carrier trapping on the efficiency of singlelayer OLEDs, we extended the device model by Davids et al [2][3][4] describing charge injection, transport, and recombination in these devices to account for charge trapping in the organic material and the effects of luminescence quenching in the region adjacent to a metal electrode. Device simulations were used to demonstrate the influences of trapping on device efficiency through their effects on charge balance, mobility balance, recombination rate, and the location of the recombination region when quenching at metallic contacts is important.…”
Section: The Effects Of Energetic Disorder and Polydispersity In Conjmentioning
confidence: 99%
“…1 There are several challenges that need to be met in order for this technology to become commercially viable and much effort is being invested to learn the parameters that control device performance. [2][3][4][5][6] Polydispersity in conjugation length, for example, is of particular importance in polymer-based OLEDs because it has been empirically linked to energetic disorder 7 and is a parameter that can be controlled prior to device fabrication. The work of Menon et al 7 demonstrates the importance of controlling polydispersity, though, in contrast to the present work, they conclude that energetic disorder can only have a negative effect on the device efficiency.…”
Section: The Effects Of Energetic Disorder and Polydispersity In Conjmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental 1 and theoretical [2][3][4][5][6][7][8][9] studies have made clear that the resulting energetic disorder of the states in between which the charge carrier hopping takes place does not only determine the temperature (T) and electric field (F) dependence of the mobility, 10 but that it also gives rise to a charge carrier density (n) dependence. Although various advanced numerical OLED device models have been developed and applied, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] so far analyses of the current density and radiative recombination in full OLEDs, taking the carrier density dependence of the mobility into account, have not yet been reported. There is an urgent need for such an OLED device model, in order to make it possible to rationally design OLEDs with improved efficiency for applications such as large-area light sources.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a lot of studies have been carried out in order to understand the basic principles of OLEDs. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, only a few theoretical studies were reported on the doped OLED. 21,22 In previous literature, we have established an electrical and optical simulation model for multilayer undoped OLED.…”
Section: Introductionmentioning
confidence: 99%